Implementation of quality management based on local wisdom on the outpatient service in the surya husadha hospital, nusa dua - Komang Maha Intan Ayu Lestari; Ketut Arnaya (Journal of Business on Hospitality and Tourism, 2021)
This research aimed to observe the implementation of quality management of hospital’s health care service and to identified whether the service done by the hospital were related to the local wisdom in its quality management implementation. This research was designed using qualitative descriptive approach which was located in Surya Husadha Hospital, Nusa Dua. The data source in this research was a primary data which was collected through the research informant. The informants in this research were the head of polyclinic, the head of health care service division, health workers, and patients. The data validation testing was done using triangulation. The data were analysed using qualitative descriptive analysis technique. The result of this research showed that the quality management implementation on the health care service through the perspective from service users had been implemented properly, from the medical service to the non-medical service. The service which had been done related to the local wisdom on its implementation, based on Tat Twan Asi. Tat Twam Asi used as a guidance in giving service to the people. And also there were other local wisdoms, which were menyama braya and tri hita karana which consists of parahyangan, pawongan, and palemahan.